Comparison of Ion–Proton Differential Speed between Interplanetary Coronal Mass Ejections and Solar Wind near 1 au - Zhang, Xuechao; Song, Hongqiang; Zhang, Chengxiao; Fu, Hui; Li, Leping; Li, Jinrong; Wang, Xiaoqian; Wang, Rui; Chen, Yao (The Astrophysical journal, 2024)
The elemental abundance of interplanetary coronal mass ejections (ICMEs) and solar wind near 1 au is often adopted to represent the abundance in the corresponding coronal sources. However, the absolute abundance of heavy ions (relative to hydrogen) near 1 au might be different from the coronal abundance due to the ion–proton differential speed ( V ip ). To illustrate the V ip characteristics and explore whether it influences the absolute abundance analysis for ICMEs and solar wind, we perform a statistical study on the V ip for He 2+ , C 5+ , O 6+ , and Fe 10+ in both ICMEs and solar wind based on measurements of Advanced Composition Explorer. The results show that the V ip is negligible within ICMEs and slow solar wind (< 400 km s −1 ), while obvious in the intermediate (400–600 km s −1 ) and fast wind (> 600 km s −1 ). Previous studies showed that the V ip in ICMEs keeps negligible during propagation from 0.3 to 5 au, but in solar wind it increases with the decreasing heliocentric distance. Therefore, it might be questionable to infer the absolute abundance of coronal sources through in situ abundance near 1 au for solar wind. Fortunately, the ion–oxygen (O 6+ ) differential speed ( V io ) is negligible for He 2+ , C 5+ , and Fe 10+ within both ICMEs and solar wind, and previous studies suggested that the V io does not vary significantly with the heliocentric distance. This indicates that various heavy ions always flow at the same bulk speed and their relative abundance (relative to oxygen) near 1 au can represent the coronal abundance for both ICMEs and solar wind.